Single-Nucleotide Polymorphisms in LEP and LEPR Associated With Breast Cancer Risk: Results From a Multicenter Case–Control Study in Chinese Females - Li, Liang; Meng, Xingchen; Liu, Liyuan; Xiang, Yujuan; Wang, Fei; Yu, Lixiang; Zhou, Fei; Zheng, Chao; Zhou, Wenzhong; Cui, Shude; Tian, Fuguo; Fan, Zhimin; et al. (Frontiers in Oncology, 2022)
Background: Leptin (LEP) plays a physiological role through its specific receptor (LEPR) and involves in the occurrence and development of breast cancer. Our current study aimed to determine the influence of single nucleotide polymorphisms (SNPs) in the genes coding for LEP and LEPR on breast cancer risk. Methods: In the present study, 963 breast cancer cases and 953 controls were enrolled. Five SNPs of LEP and two of LEPR were chosen to evaluate the correlation of selected SNPs with breast cancer susceptibility among women in northern and eastern China. Analyses were further stratified by body mass index (BMI), waist-hip rate (WHR), estrogen receptor and progesterone receptor status. The expression pattern of risk variants associated gene were detected by expression Quantitative Trait Loci (eQTL) analysis with eQTLGen and the cancer genome atlas database. Results: There were significant differences between breast cancer cases and control groups in menopausal status and family history of breast cancer. Two SNPs (rs1137101 and rs4655555) of LEPR gene decreased overall breast cancer risk, and other five SNPs showed no significant association with breast cancer risk. rs1137101 (GA vs GG; adjusted OR = 0.719, 95% CI = 0.578-0.894, P = 0.003) and rs4655555 (TT vs AA; adjusted OR = 0.574, 95% CI = 0.377-0.873, P = 0.009) significantly decreased breast cancer risk after Bonferroni correction for multiple testing. In subgroup analyses, the GA and GA + AA genotypes of LEPR rs1137101 associated with decreased breast cancer risk in subgroup of BMI ≤ 24 kg/m2 or WHR ≥ 0.85 after Bonferroni correction. Furthermore, we found that the expression of rs4655555 associated gene LEPR and leptin receptor overlapping transcript (LEPROT) were upregulated in breast cancer tumor tissues compared with adjacent normal tissues, and higher expression of LEPR in tumor tissues was correlated with poor prognosis of breast cancer patients using The Cancer Genome Atlas Breast Invasive Carcinoma (TCGA-BRCA) data. Conclusion: Our study demonstrated that the polymorphism rs1137101 and rs4655555 located in LEPR gene decreased breast cancer risk in Chinese females, which might be a research-worthy bio-diagnostic marker and applied for early prediction and risk assessment of breast cancer.